Use of Force by the Montgomery County, Maryland Police Department, 1993-1999 - Garner, Joel H. ([Verlag nicht ermittelbar], 2004)
This study was designed to describe the types and amount of force used by and against the police in Montgomery County, Maryland, for the seven years between January 1993 and December 1999. The researchers collected data from the Montgomery County Police Department's Use of Force Reports and arrest records for this time period. Part 1 contains data obtained from the Use of Force Reports, including information about the characteristics of the force used, injuries and medical treatment, characteristics of the officer and citizen involved, and the time and date of the incident. Part 2 contains data from the arrest records, including variables for location, time, and date of the arrest, the most serious charge, and demographic characteristics of the officer and arrestee. Part 3 contains aggregate data, including rate of force by different arrest characteristics, that were derived from the data in Parts 1 and 2.